PENGARUH PENERAPAN MODEL PBL TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI “NORMA” KELAS V SEKOLAH DASAR - Widiyastuti, Indry; Rondli, Wawan Shokib; Ismaya, Erik Aditia (Universitas Muria Kudus, 2024)
It was found that there is a problem with the lack of innovative teaching models used by teachers. The purpose of this study is to examine the influence of the implementation of the Problem-Based Learning (PBL) model on students' learning outcomes in the subject of Pancasila Education, specifically on the